Effect of andrographis paniculata leaf extract on wound healing in rats - Al-Bayaty, F.H.; Ali, Hapipah Mohd; Hassan, M.I.A.; Abdulla, M.A. (Taylor & Francis, 2012)
This work was carried out to study the effect of topical application of Andrographis paniculata on the rate of wound enclosure and its histological features. A wound was created in four groups of rat in posterior neck region. Blank placebo was applied topically to the wounds of Group 1. Groups 2 and 3 were dressed with placebo containing 5% and 10% extracts of A. paniculata, respectively. Intrasite gel was applied topically to the wounds of Group 4. Macroscopical examination revealed that the rate of wound healing was significantly accelerated in the wound dressed with A. paniculata extract compared to the blank placebo. The wounds dressed with 10% extract or Intrasite gel healed earlier compared to the wounds dressed with placebo containing 5% A. paniculata extract. Histologically, wounds dressed with A. paniculata extracts showed markedly less scar width and contained large amounts of fibroblast proliferation. More collagen and less angiogenesis with absence of inflammatory cells were seen for wounds dressed with 10% A. paniculata compared to the blank placebo. Conclusion, A. paniculata extracts significantly enhanced rate of wound healing in rats. © 2012 Taylor & Francis.